Tharīqatu Ta’līm Qawā’id al-Lughah al-‘Ārabiyyah baina al-Qadīmah wa al-Hadītsah - Haniatul Mabruroh (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
Tharīqatu Ta’līm Qawā’id al-Lughah al-‘Ārabiyyah baina al-Qadīmah wa al-Hadītsah Hani’atul MabrurohUniversity of Darussalam Gontorhannimabrur@gmail.com Abstract            Arabic grammar is an essential component to learn to contain Nachwu, Sharaf, Insya’, etc. It is regarded as important because correct grammar contributes to a correct understanding of speaking, writing, and reading skills. As an attempt to reach that objective, schools have used different teaching methods. Some of them have chosen old and modern methods for teaching the Arabic grammar according to the needs of the schools as well as various circumstances. The modern method has been used in the field of Arabic Language Teaching for communication. It is in the form of discussion and representation techniques for learning which aims the students to get back to the interaction of life and sensory movements. The method has an important role to play in the educational process since it is one way to communicate information to the students.  Therefore, schools have to prepare teachers who are proficient in teaching and speaking Arabic because teachers’ spirit is one of the essential foundations of education.Keyword: Arabic grammar, old method, modern method, teaching method طريقة تعليم قواعد اللغة العربية بين القديمة والحديثة هنيئة المبرورةجامعة دار السلام كونتورhannimabrur@gmail.com ملخصقواعد اللغة العربية من أهم الأمور يجب تعلمها، تحتوي على النحو والصرف والبلاغة والإنشاء وغير ذلك. هو مهم لأن صحة القواعد تحقق صحة الكلام والكتابة والقراءة وتحقق صحة المعنى المقصود. بعظمة أهميتها، قامت المدارس على تعليمها بطريقة مختلفة. اختار بعضها الطريقة القديمة وبعضها الطريقة الحديثة، حسب احتياجات المدرسة إليها بنظر إلى ظروف شتى. ظهور الطريقة الحديثة لا يخلو من وظائف تعليم اللغة العربية وهي وسيلة الاتصال، وإدخال أسلوب المحاورة والمناقشة والتمثيل. وذلك لتعود المتعليمن على التفاعل بالحياة والحركة الحسية. فحاول المتخصصون في تعليم اللغة على إجاد الطريقة الجديدة التي اتخذت الأساليب السابقة في التعليم. فبهذا، للطريقة دور مهم في العملية التعليمية، وأنها شامل باستخدام وسائل التعليم والمهارات فيه. تعتبر أن الطريقة هي وسيلة لايصال المعلومات إلى المتعلمين. فيجب على المدرسة إعداد المدرسين ذو الكفاءة في التعليم والتكلم باللغة العربية الفصيحة، لأن روح المدرس من أهم أساس تعليم..الكلمة الرئيسية: قواعد اللغة العربية، الطريقة القديمة، الطريقة الحديثة، طريقة التعليم